Pemberdayaan Anak dan Remaja dalam Pengoptimalan Taman Fontabaca sebagai Upaya Menumbuhkan Minat Literasi Membaca di Fontania Desa Tambun - Khasanah, Fata Nidaul; Lestari, Rini Dwi; Dalim, Dalim; Nugroho, Alfian Dwi; Syaumi, Muhammad Rizki; Ramadhansyah, Rafli; Ramadhan, Fahri; Rizki, Faisal Muhammad; Prasojo, Prasojo (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The better the literacy of the people, the better the level of thinking and the achievement of the progress of the community in various aspects of life. However, in reality our current literacy culture is still low. Currently the partner has a side of the reading garden established in 2021 known as Fontabaca Park. But unfortunately, the establishment of a reading garden was not fully utilized by children and teenagers. This is exacerbated by the lack of reading material available in the reading garden. The lack of interest in reading or borrowing books is partly due to the lack of socialization related to literacy activities to children and adolescents in the Fontania region. The method of implementing activities starts from counseling, training, mentoring and evaluation. The results of each stage of the implementation activity start from the counseling activities carried out by analyzing the problem then continued with mapping the solutions provided for partners. Followed by providing training activities related to reading literacy and the formation of reading garden cadres. Mentoring activities are in the form of procurement of needed reading book materials and involving participants to label and collect reading books. Evaluation activities obtained an average percentage of 98% of the impact of activities carried out by the implementation team as an effort to optimize the existing Fontabaca park.